1998
DOI: 10.4269/ajtmh.1998.59.202
|View full text |Cite
|
Sign up to set email alerts
|

The time course of cytoadhesion, immunoglobulin binding, rosette formation, and serum-induced agglutination of Plasmodium falciparum-infected erythrocytes.

Abstract: Abstract. We describe morphologic characteristics of acridine orange-stained Plasmodium falciparum-infected erythrocytes and the sequential expression of several adhesion phenomena. In particular, we have studied when the adhesive and antigenic modifications appear on the infected erythrocyte surface that mediate binding to C32 melanoma cells (cytoadherence) or to erythrocytes (rosette formation) during a complete 48-hr life cycle of the parasite. The C32 melanoma cell binding started at about 12 hr and was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…This study further emphasizes the importance of human serum during the cultivation of P. falciparum isolates and laboratory strains to guarantee the display of the parasite’s adhesive phenotype and correct expression of PfEMP1. Various parasite lines depend on human immunoglobulins for the formation of rosettes [23], [34], [35], [36], [38], [44]; in addition, rosetting requires complementary serum factors [37]. Studies investigating the rosetting phenomena need to take into consideration that the display of the rosetting phenotype and expression of PfEMP1, and possibly other parasite ligands, can be dependent on the presence of human serum.…”
Section: Discussionmentioning
confidence: 99%
“…This study further emphasizes the importance of human serum during the cultivation of P. falciparum isolates and laboratory strains to guarantee the display of the parasite’s adhesive phenotype and correct expression of PfEMP1. Various parasite lines depend on human immunoglobulins for the formation of rosettes [23], [34], [35], [36], [38], [44]; in addition, rosetting requires complementary serum factors [37]. Studies investigating the rosetting phenomena need to take into consideration that the display of the rosetting phenotype and expression of PfEMP1, and possibly other parasite ligands, can be dependent on the presence of human serum.…”
Section: Discussionmentioning
confidence: 99%
“…The number of oncospheres adhering to viable monolayer CHO-K1 cells was compared to the number of oncospheres adhering to fixed monolayer CHO-K1 cells after 48 h of cell culture. The fixed monolayer CHO cells were treated with 1% formaldehyde for 1 h and subsequently stored in PBS at 4°C until they were used (34). Viable and fixed monolayer cells were incubated with 2,500 T. solium activated oncospheres in binding medium at 37°C for 1.5 h. After incubation, the unbound oncospheres were rinsed three times with binding medium, and the oncospheres bound to the cells were fixed with 1% glutaraldehyde in PBS and stained with PAS.…”
Section: Methodsmentioning
confidence: 99%
“…Why nonimmune Igs bind to the pRBC surface remains to be explained. In several subsequent investigations, it was found that a majority of rosetting parasites engage in Ig-binding activities, but some nonrosetting parasites also bind IgM and/or IgG (109,110,118). Some pRBCs bind only one class of Ig (IgM or IgG), while most bind both classes of Igs.…”
Section: Serum Proteins Involved In Rosette Formationmentioning
confidence: 99%